URGENSI PENGATURAN DATA DIGITAL/ ELEKTRONIK PRIBADI - Susanto, Deny (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Regulation of Personal Data is a type of legal protection for individual citizens that is urgently required in Indonesia right now. This protection is needed in all spheres of community life, including business activities and other fields of life, where data processing relating to individuals concerning identity, whether confidential or not, is involved. In order to understand the urgency and effective management of personal data protection in Indonesia, this research uses normative legal research to review regulatory rules related to data protection. It is hoped that this research will result in the formulation of a comprehensive regulation on protection arrangements and private information in Indonesia